PENGARUH KOMPOSISI PEREKAT FENOL FORMALDEHIDA TERHADAP.KETEGUHAN REKAT KAYU LAPIS SENGON - Rodjak Memed; Adi Santoso; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1990)
In the future. phenol formaldehyde resin will be used in greater quantity due to ita capability inproducing weather and boil•proof plytDood. This paper discribet two aapects, i.e. ':  the effect of weight ratio of phenol and formaldehyde on the propemea  of phenol formaldehyde  resin and plywood  bonding strength; and the effect of filler proportion on the bond.inf ltrength of se111on plywood glued with phenol formaldehyde.77ae resulta showed that the properties of phenol formaldehyde resin which were produced in three different com- positions were met  Indonesian Standard. The effect of filler proportion on plywood  bonding strenfth waa significant, but the effect  of  weight ratio of phenol  formaldehyde and their interaction were not significant. The bond.inf strength of plywood  glued .with phenol  formaldehyde at 1111  compositio1u were conformed   with German standard for exterior ply- wood. The_ rwlati_onship between filler proportion and plywood  bonding strength could be exprwued by quadratic regreBBion.